2016
DOI: 10.1007/s12671-016-0581-1
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Mindfulness into Positive Psychology: a Randomised Controlled Trial of an Online Positive Mindfulness Program

Abstract: Abstract:The purpose of the present study was to test the efficacy of an 8-week online intervention-based Positive Mindfulness Program (PMP) that integrated mindfulness with a series of positive psychology variables, with a view to improving wellbeing scores measured in these variables. The positive mindfulness cycle, based on positive intentions and savouring, provides the theoretical foundation for the PMP. The study was based on a randomised wait-list controlled trial; and 168 participants (128 females, mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
71
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 59 publications
11
71
0
Order By: Relevance
“…In light of these results, it is possible that the MBI was more useful in allowing Mike to live in the present moment and to notice positive events in his life, leading him to increased happiness levels, rather than impacting directly on his depressive symptoms (Brown 2015;Brown and Ryan 2003). Our results also support those from past research in adult populations, showing that a mindful state is related to positive variables such as well-being, happiness, positive affect, self-regulation, compassion and autonomy (Brown and Ryan 2003;Friese and Hofmann 2016;Ivtzan et al 2016;Lau et al 2006). Finally, they complement results of Schonert-Reichl et al's (2015) study of elementary school children showing that a MBI increased levels of optimism, emotional regulation and empathy.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In light of these results, it is possible that the MBI was more useful in allowing Mike to live in the present moment and to notice positive events in his life, leading him to increased happiness levels, rather than impacting directly on his depressive symptoms (Brown 2015;Brown and Ryan 2003). Our results also support those from past research in adult populations, showing that a mindful state is related to positive variables such as well-being, happiness, positive affect, self-regulation, compassion and autonomy (Brown and Ryan 2003;Friese and Hofmann 2016;Ivtzan et al 2016;Lau et al 2006). Finally, they complement results of Schonert-Reichl et al's (2015) study of elementary school children showing that a MBI increased levels of optimism, emotional regulation and empathy.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, given that it is not possible to live a life devoid of unpleasant and stressful events, it is possible that the MBI helped Mike increase his happiness by increasing his awareness of positive experiences and by building his resilience to stress (Wong 2011). Accordingly, past research has suggested that MBIs have an impact on well-being by bringing awareness to and enhancing the savoring of day-to-day experiences (Garland et al 2015;Ivtzan et al 2016;Lindsay and Creswell 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further exploration of meditation reveals an intervention with a broad range of beneficial psychological effects. According to a recent mindfulness review 23,24 among others these include positive affect, cognitive flexibility, and emotional regulation. In addition, meditative approaches commonly provide mechanisms for facing or approaching, rather than avoiding difficulty.…”
Section: Resilience Interventionsmentioning
confidence: 99%